Sociological Aspects Of Eyes In The Land Of Melus And Their Relevance To Indonesian Language Learning - Hidayah, Alfia Nurul; Pujiarti, Pujiarti (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the sociological aspects of literature contained in the novel Mata di Tanah Melus by Okky Madasari, its social functions, and its relevance to Indonesian language learning in Madrasah Tsanawiyah. Methodology: This study used a qualitative descriptive method. Data were collected from the novel Mata di Tanah Melus and interviews with informants including educators and students. Data collection employed content analysis and in-depth interviews. Data were validated using source and theory triangulation, and analyzed using an interactive model and literary sociology approach based on Ian Watt's theory. Main Findings: The study found socio-cultural aspects in the novel including knowledge systems, beliefs, kinship, tools and livelihood systems, and language. Social functions of the novel were reflected in positive reader responses indicating moral and educational value. The novel was also found to be relevant to Indonesian language learning, particularly in appreciation and review of literary texts aligned with the 2013 curriculum for Madrasah Tsanawiyah. Novelty/Originality of this study: This study uniquely integrates literary sociology analysis with educational application by linking the socio-cultural content of a children's fantasy novel to curriculum-based Indonesian language instruction. It provides a model for using literary texts with cultural depth in character-building education at the junior secondary level.